2020
DOI: 10.3390/cancers12051178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Whole Genome Data on Therapeutic Decision-Making in Metastatic Prostate Cancer: A Retrospective Analysis

Abstract: Background: While critical insights have been gained from evaluating the genomic landscape of metastatic prostate cancer, utilizing this information to inform personalized treatment is in its infancy. We performed a retrospective pilot study to assess the current impact of precision medicine for locally advanced and metastatic prostate adenocarcinoma and evaluate how genomic data could be harnessed to individualize treatment. Methods: Deep whole genome-sequencing was performed on 16 tumour-blood pairs from 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 125 publications
1
20
0
Order By: Relevance
“…The numbers of SVs simulated were based on previous studies that have suggested the presence of 5,000 to 10,000 polymorphic SVs in the human genome [ 15 ] and between a handful to up to 1000 somatic SVs across a range of tumour types [ 16 ]. These findings support what we have also observed in our own work [ 17 , 18 ]. It is worth noting that, very similar results were observed when the number of germline SVs were reduced to match the number of somatic SVs except for two callers ( S1 File ).…”
Section: Methodssupporting
confidence: 94%
“…The numbers of SVs simulated were based on previous studies that have suggested the presence of 5,000 to 10,000 polymorphic SVs in the human genome [ 15 ] and between a handful to up to 1000 somatic SVs across a range of tumour types [ 16 ]. These findings support what we have also observed in our own work [ 17 , 18 ]. It is worth noting that, very similar results were observed when the number of germline SVs were reduced to match the number of somatic SVs except for two callers ( S1 File ).…”
Section: Methodssupporting
confidence: 94%
“…Some prior studies have begun to demonstrate the utility of Bionano UHMW DNA isolation protocols in solid tissue tumor analysis. These include studies of lung squamous cell carcinoma and metastatic prostate carcinoma [7,34,35]. This current report demonstrates the utility of the a DNA isolation protocol and SV analysis in a wide variety of solid tissue types, and expands the feasibility of such analysis for previously unused human tissue types.…”
Section: Discussionmentioning
confidence: 72%
“…Despite its success in visualizing SVs in liquid tumors and cell lines, OGM has not yet seen widespread application in solid tissue tumors, due primarily to the difficulty of obtaining high-quality, high-molecular-weight DNA from solid tumor samples. Nonetheless, previous work has shown the feasibility of high-quality high-molecular-weight DNA isolation and analysis using earlier workflow iterations [ 33 ], and recent feasibility studies have shown the importance of OGM application to solid tumor analysis [ 7 , 34 , 35 ]. Peng et al demonstrated large SVs not detected by WGS implicated in metastatic lung squamous cell carcinoma [ 7 ], and Jaratlerdiri et al and Crumbaker et al similarly found SVs impacting oncogenic and tumor-suppressing genes not identified by NGS or WGS alone in prostate cancer [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%